Damage mechanisms of two-stage concrete exposed to chemical and physical sulfate attack. (15th April 2017) - Najjar, M.F.; Nehdi, M.L.; Soliman, A.M.; Azabi, T.M.
Highlights: Damage mechanisms of TSC under chemical sulfate and physical salt attacks explored for the first time. TSC made with silica fume incurred severe thaumasite attack, which warrants future investigation. Conflicting effects of SCMs on concrete chemical/physical sulfate attack need concerted research. Promising effect of metakaolin in TSC under chemical/physical sulfate exposures needs validation. Abstract: There is currently dearth of information on the durability of two-stage concrete (TSC) to physical and chemical sulfate exposure. TSC differs from conventional concrete in many ways including its placement technique, high aggregate content and the use of very flowable grout. Therefore, available data on the behavior of conventional concrete under sulfate attack may not be applicable to TSC. For instance, the effects of different parameters such as the addition of supplementary cementitious materials (SCMs) on the resistance to sulfate attack are well documented for conventional concrete; however, for TSC this has not been duly investigated. In this study, the behavior in sodium sulfate laden environments of TSC mixtures incorporating different SCMs as partial replacement for ordinary Portland cement (OPC) was investigated. Two different sodium sulfate exposure regimes were studied: full immersion simulating chemical sulfate attack, and partial immersion combined with cyclic temperature and relative humidity, which is conducive to physical salt attack. Fully immersed TSC specimens incorporating fly ash or metakaolin exhibited high sulfate resistance. Surprisingly, TSC specimens incorporating silica fume exhibited significant damage due to thaumasite formation. Under exposure to physical salt attack, TSC specimens incorporating fly ash and/or silica fume incurred severe surface scaling at the evaporative front, while those made with metakaolin unveiled adequate resistance to surface scaling. An attempt has been made to delineate the mechanisms which explain such observed behavior.